Students’ Difficulties in Writing Recount and Narrative Text - Rodia Mestina Simare mare; Herman Herman; Christian Neni Purba; Bloner Sinurat; Nanda Saputra (Jurnal Scientia, 2022)
The aim in this research is to find out the students’ difficulties in writing recount and narrative text at eleventh grade of SMAS HKBP Sidorame. This research the researchers used descriptive qualitative. The data sources of this research take from students writing that the researchers come to their school. The data of this research are students writing that have students’ difficulties in recount and narrative text by students SMAS HKBP Sidorame. The instrument collecting data used documentation in the form of students writing, and for technique collecting data is documentation method in the form of written document. The result/ findings that the students’ difficulties in writing were mostly found in grammar (69), vocabulary (27), handwriting (0), punctuation (1), spell (0). Student’s difficulties are an unintentional act of someone in writing which results in a sentence or story not having a good structure and making it difficult for readers and listeners to understand. The researchers conclude that most of the students '' difficulties in writing are in grammar because of the lack of understanding in the preparation of sentences besides the lack of students in vocabulary because as we know in English, they must have a lot of vocabulary.